Managing Performance of Mutual Funds During Different Phases of a Business Cycle in India - Rathore, Shubhkamna; Singh, Sukhdev (Indian Journal of Finance, 2017)
The present study evaluated the performance of mutual funds (sector wise) in India over a period of 11 years (2003 to 2014) using performance indicators such as Sharpe ratio, Jensen alpha, and Treynor's ratio. The analysis consisted of 54 schemes out of which 27 schemes are offered by nine private sector mutual fund companies; 12 schemes are offered by four public sector companies ; and 15 schemes are offered by five foreign sector mutual fund companies. The entire study period is classified into three sub-periods based upon the movement of the Sensex named as pre-period, inter- period, and post-period. Effect of different economic situations during these time periods with reference to selected mutual fund schemes of public, private, and foreign sectors has been studied on the basis of risk and returns parameters. The study evidenced that the private sector performed well as compared to the public and foreign sector in the pre and post period. Among the schemes, equity performed better as compared to balanced and tax saving schemes and during the inter period, public, private, and foreign sector AMCs moved according to the market against the expectations of the investors.